Abdominal tuberculosis: a clinicopathologic study in Kashmir valley - Kumar, Ravinder; Digra, Madhu; Kumar, Dinesh (International Surgery Journal, 2017)
Background: Tuberculosis is a major health hazard in India. Because of its diverse manifestations, difficult diagnosis, widespread complications, prolonged morbidity and increased mortality the study of this disease becomes even more important. The objectives of the study were to study age and sex distribution of abdominal tuberculosis, to study association of abdominal tuberculosis with pulmonary tuberculosis, to study various clinical presentations of abdominal tuberculosis, to study various modalities for diagnosis of abdominal tuberculosis and to study the surgical management in relevant patients of abdominal tuberculosis. Methods: This study was carried out in 50 patients of abdominal tuberculosis of different age group and sex admitted in Department of Surgery, SMHS Hospital, Govt. Medical College, Srinagar during the period from 2002 to 2004. The patients of abdominal tuberculosis fell into two broad categories - those presenting with acute/sub-acute intestinal obstruction and those without obstruction. All patients were worked up with the elicitation of proper history, clinical examination, laboratory investigation, etc. The diagnosis was confirmed by IgM ELISA for tuberculosis, peritoneocentesis, FNAC, laparotomy and biopsy of the specimen obtained at the time of surgery. Results: Maximum incidence of abdominal tuberculosis was noted in third and fourth decades followed by second decade of life. Males constituted 60% and females constituted 40% of total patients. 23 patients presented with acute and 27 patients with chronic onset of signs and symptoms respectively. Abdominal pain, anorexia, weight loss, weakness, vomiting and constipation were the main presenting symptoms. No haemoglobin and raised ESR were the commonest finding on routine laboratory investigations in majority of the patients. IgM ELISA for tuberculosis was positive in 41 patients (95.34%). Surgical intervention was required in 50% of the patients. Conclusions: Good clinicopathological workup in patients of abdominal tuberculosis results in earlier diagnosis and timely management of this curable disease.